Philippe de Commynes : Memory, Betrayal, Text - Kleiman, Irit Ruth, 1973- (Book collections on Project MUSE., 2013)
This study significantly deepens our understanding of how historical narrative and diplomatic activities are intertwined in the work of this iconic, iconoclastic figure.